Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
The Selected Issues paper provides an estimate of the output gap and potential output for Italy, and examines the sensitivity of the results to assumptions regarding employment and productivity growth. The paper focuses on the labor market more directly by examining the linkages between wage bargaining systems, regional wage differentiation, and regional unemployment disparities. It also provides an assessment of the government's tax reform program, including its potential to increase incentives for employment and investment.